PERAN DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI DALAM PENYELENGGARAAN HUBUNGAN INDUSTRIAL DI KAB. INDRAGIRI HULU - Mardiansyah, Ogi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Worker or laborer is quite important corporate asset, but in fact often the things that can cause industrial relations problems such as lack of remuneration, termination of employment, and so on. Therefore, the local government through establishing government agencies related to the Social Service Manpower Indragiri Hulu acts as a mediator organization of industrial relations should be able to play an active role in helping to resolve the existing problems in Indragiri Hulu. To determine the role of the Social Department of Manpower and Transmigration as the organization of industrial relations in Indragiri Hulu, the authors conducted a study entitled